2006
DOI: 10.1158/1078-0432.ccr-06-0836
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Decay-Accelerating Factor CD55 as a Peanut Agglutinin–Binding Protein and Its Alteration in Non–Small Cell Lung Cancers

Abstract: Purpose: Peanut agglutinin (PNA) recognizes tumor-associated carbohydrates. In this study, we aimed to identify the core protein harboring PNA-binding sugars in the human lung and to explore the relationship with the pathology of primary non^small cell lung cancers (NSCLC). Experimental Design: PNA lectin blotting was used to detect PNA-binding proteins in the microsomal fraction of lung tissue from 24 patients with NSCLC. The 55-to 65-kDa core peptide PNA-binding protein was characterized by enzymatic treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…CD55 also inhibits C3 and C5 activation and thereby limits complement-dependent cell cytotoxicity (CDC) [10, 13]. Studies have demonstrated a down-regulation of CD55 in NSCLC cells [17]. Our present results supported that the CD55 rs2564978 CC genotype was linked to an increased risk of NSCLC.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…CD55 also inhibits C3 and C5 activation and thereby limits complement-dependent cell cytotoxicity (CDC) [10, 13]. Studies have demonstrated a down-regulation of CD55 in NSCLC cells [17]. Our present results supported that the CD55 rs2564978 CC genotype was linked to an increased risk of NSCLC.…”
Section: Discussionsupporting
confidence: 84%
“…The expression CD55 in gastric cancer, colon and breast cancer was significantly greater than in those non-cancer tissues [1216]. However, studies also demonstrated a down-regulated expression of CD55 in ovarian cancer and lung cancer tissues [17, 18]. In Higuchi's study, CD55 was recognized as a novel PNA-binding protein in the human lung and the down-regulation of CD55 was associated with pathology of primary NSCLC [17].…”
Section: Introductionmentioning
confidence: 99%
“…There might be a differential effect of CD55 between healthy and cancer cells at play here, as CD55 in NSCLC is not only down-regulated, but also sialylated. Possibly, sialylated CD55 can execute its function longer than regular CD55, as it has a high resistance against proteolysis and can thus be retained on the cell surface for a longer time ( 153 ). Another explanation could be that NSCLC tissue does not require complement regulation as much, as the bulky tissue formation ensures that not all cells are exposed to the alveolar cavity, and thus to complement activity ( 153 ).…”
Section: The Role Of Complement Regulators In Pathologiesmentioning
confidence: 99%